(untitled) (Research, Society and Development, 2022)
Burnout Syndrome is a psychosocial disease that occurs due to a chronic response from generated stress work environment, affecting workers from different areas, being more susceptible in professions that has competitiveness and high workloads, including healthcare professionals. This is a bibliography review study with the objective to investigate work conditions and the possible correlation of these with the Burnout Syndrome in healthcare professionals. Articles from the PePSIC, PubMed, SciELO and Capes Journals databases, published between 2015 and 2021, that used the Maslach Burnout Inventory in the burnout among healthcare professionals. The results showed a prevalence of burnout among healthcare professionals. Regarding the main risk factors for burnout, there were work overload, high demand of daily patients, night shifts, high number of care per shift, leading these professionals to develop a negative self-image of their performance and dissatisfaction with work. It is suggested to consider the biopsychosocial and the working conditions factors in the prevetion of Burnout Syndrome among the heathcare professionals.